2012
DOI: 10.1159/000343339
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Suicidal Erythrocyte Death by Ipratropium Bromide

Abstract: Background/Aims: Ipratropium bromide, an anticholinergic agent widely used in obstructive lung disease, has previously been shown to trigger suicidal death of nucleated cells or apoptosis. Despite their lack of mitochondria and nuclei, key organelles in the execution of apoptosis, erythrocytes may similarly undergo suicidal cell death, which is characterized by cell shrinkage and by cell membrane scrambling with phosphatidylserine-exposure at the cell surface. Triggers of eryptosis include increase of cytosoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…A recent clinical study also correlated the use of anti-muscarinics with adverse cardiovascular outcomes in patient trials (Liou et al, 2018), therefore indicating adverse cardiovascular effects with drug use. In particular, Ipratropium bromide, a short acting anti-muscarinic has been shown to exacerbate myocardial ischaemia/reperfusion injury in an in vitro whole heart model (Harvey et al, 2014) and initiate calcium mediated suicidal cell death of erythrocytes (Shaik et al, 2012), indicating the occurrence of intercellular signalling otherwise not ascribed to antagonists.…”
Section: Introductionmentioning
confidence: 99%
“…A recent clinical study also correlated the use of anti-muscarinics with adverse cardiovascular outcomes in patient trials (Liou et al, 2018), therefore indicating adverse cardiovascular effects with drug use. In particular, Ipratropium bromide, a short acting anti-muscarinic has been shown to exacerbate myocardial ischaemia/reperfusion injury in an in vitro whole heart model (Harvey et al, 2014) and initiate calcium mediated suicidal cell death of erythrocytes (Shaik et al, 2012), indicating the occurrence of intercellular signalling otherwise not ascribed to antagonists.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the known co-morbidities, to our knowledge there have been no non-clinical investigations to date to assess the effects of anticholinergic compounds, such as ipratropium, in the setting of simulated IHD or MI. Further to this, Shaik et al (2012) have recently demonstrated that ipratropium is capable of eliciting suicidal erythrocyte death (eryptosis) via a mechanism due to stimulation of increased cytosolic Ca 2+…”
Section: Ipratropium Bromide Mediated Myocardial Injury In In Vitro Mmentioning
confidence: 93%
“…activity (Shaik et al, 2012). Despite differences between eryptosis and apoptosis, which only occurs in nucleated cells, both of these processes can be initiated by increases in Ca 2+ concentration, indicating that ipratropium may have the ability to also trigger apoptosis.…”
Section: Ipratropium Bromide Mediated Myocardial Injury In In Vitro Mmentioning
confidence: 99%
“…Triggers of eryptosis may include increase of cytosolic Ca 2+ activity ([Ca 2+ ] i ) [34], formation of ceramide [35], energy depletion [34], activated caspases [36,37,38,39,40], activation of casein kinase 1α [41,42], Janus-activated kinase JAK3 [43], protein kinase C [44], or p38 kinase [45], as well as impaired activity of AMP activated kinase AMPK [46], cGMP-dependent protein kinase [37], PAK2 kinase [47], sorafenib sensitive kinases [48], and sunitinib sensitive kinases [49]. Moreover, eryptosis is stimulated by a wide variety of xenobiotics [35,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79] including several natural substances [34] including gambogic acid [80], tannic acid [81], ipratropium [82], withaferin [83], tanshinone [58], thymoquinone [84], ursolic acid [85], honokiol [86], saponin [87], apigenin [88], oridonin [89], and alpha-lipoic acid [36]. …”
Section: Introductionmentioning
confidence: 99%